Multicountry Distribution and Characterization of Extended-spectrum β-Lactamase–associated Gram-negative Bacteria From Bloodstream Infections in Sub-Saharan Africa. (30th October 2019) - Toy, Trevor; Pak, Gi Deok; Duc, Trung Pham; Campbell, James I; El Tayeb, Muna Ahmed; Von Kalckreuth, Vera; Im, Justin; Panzner, Ursula; Cruz Espinoza, Ligia Maria; Eibach, Daniel; Dekker, Denise Myriam; Park, Se Eun; et al.
Abstract: Background: Antimicrobial resistance (AMR) is a major global health concern, yet, there are noticeable gaps in AMR surveillance data in regions such as sub-Saharan Africa. We aimed to measure the prevalence of extended-spectrum β-lactamase (ESBL) producing Gram-negative bacteria in bloodstream infections from 12 sentinel sites in sub-Saharan Africa. Methods: Data were generated during the Typhoid Fever Surveillance in Africa Program (TSAP), in which standardized blood cultures were performed on febrile patients attending 12 health facilities in 9 sub-Saharan African countries between 2010 and 2014. Pathogenic bloodstream isolates were identified at the sites and then subsequently confirmed at a central reference laboratory. Antimicrobial susceptibility testing, detection of ESBL production, and conventional multiplex polymerase chain reaction (PCR) testing for genes encoding for β-lactamase were performed on all pathogens. Results: Five hundred and five pathogenic Gram-negative bloodstream isolates were isolated during the study period and available for further characterization. This included 423 Enterobacteriaceae. Phenotypically, 61 (12.1%) isolates exhibited ESBL activity, and genotypically, 47 (9.3%) yielded a PCR amplicon for at least one of the screened ESBL genes. Among specific Gram-negative isolates, 40 (45.5%) of 88 Klebsiella spp., 7 (5.7%) of 122 Escherichia coli, 6 (16.2%) of 37 Acinetobacter spp., and 2 (1.3%) of 159 of nontyphoidal Salmonella (NTS) showed phenotypic ESBL activity. Conclusions: Our findings confirm the presence of ESBL production among pathogens causing bloodstream infections in sub-Saharan Africa. With few alternatives for managing ESBL-producing pathogens in the African setting, measures to control the development and proliferation of AMR organisms are urgently needed.